How's Knowledge, Attitudes, Family Roles, and Source of Information as Risky on Premarital Sex Behavior? - Welsy Apriliani; Dwie Yunita Baska; Lusi Andriani; Diah Eka Nugraheni; Sri Nengsi Destriani (CV Media Inti Teknologi, 2024)
Risky sexual behavior in adolescents has been identified as being unsafe without legal marriage ties and may lead to various health problems. This integrative review aimed to identify and discuss the determinants of factors related to premarital sex behavior in adolescents. The evaluation was carried out in 14 studies that met the inclusion criteria. The factors evaluated consist of knowledge, attitudes, family roles, and individual information sources. This systematic review study used the PRISMA protocol with several databases, including CINAHL, DOAJ, Scopus, Garuda, Google Scholar, and PUBMED in the 2015-2020 year of publication. It found that there was a significant relationship among those four factors, which is knowledge, attitudes, family roles, and sources of information on premarital sex behavior in adolescents. The conclusion of this study it is strongly recommends that promoting healthy premarital sex behavior can be reached by utilizing education promotion strategies for adults, the quality of family parenting, and a smart use of technology.